Representações sociais das famílias sobre Violência física na infância: como froma de educação - Miguir Terezinha Vieccelli Donoso (2006)
This study addresses physical violence against children, from parents or guardians perspective, using theoretical and methodological principals of social representations. Two research corpuses have been organized. In the first one, mothers, fathers or guardians of pre-school or school age children, have been interviewed. In this group the interviewees were not subjects of formal complaint of physical violence against their offspring. This part of the study was conducted in a city health care in Belo Horizonte. In the second corpus, the interviewees were mothers, fathers or guardians with previous record of formal complaint for physical abuse and neglect against children or teenagers who were controlled. The approach to the parents was made with the aid of a program from the Belo Horizonte City Hall Department of Well-being and Social Action, which aims mainly at the family well-being. This research project has been approved by the UFMG committee of ethics in research (COEP) and by the Belo Horizonte Health Department Committee of Ethics in Research (CEP SMSA/PBH). The participants have been invited to talk about children upbringing and the need to set limits to them: parents thoughts about it and how their experiences were. Semi-structured interviews have been used since it was considered a more adequate technique to the objectives of this study. These interviews have been analyzed using discourse analysis. The semi-structured interview scripts used different questions but both corpuses were grouped likewise in four major themes which were divided in categories that may or not have been separated in subcategories. The referred themes were: what bringing up children means, ways of bringing up, beliefs about physical punishment and reasons for it. The results found show that as far as the meaning of upbringing is concerned, there is a mixture of concepts such as education, upbringing and caretaking in the social thought. The ways of bringing children up were found to be varied in both corpuses and involve establishing rules to maintain authority, talking and using punishment either physical or not. Cultural inheritance has been noticed as strong component in the process of raising children since there seems to be a tradition in the family although it is not always a conscious one. Parents attitudes are actions or reactions to experienced relations. It was observed that physical punishment in children is a well accepted practice and that it is not always understood as violent behavior. It was also noticed that physical abuse is not always notified since in the corpus 1 there are reports of violent acts (hitting with sticks or belts, etc.) whereas there was no formal complaint about them in any of the cases. All the interviewees admit having used physical punishment on their children. It was perceived that a hard and mean reality is imposed on some children. In many cases, the home and the family do not provide them with safety, protection and kindness.